Communicating development innovation in North Sumatra via group communication - Muhammad Alfikri (Faculty of Communications Science, Dr. Soetomo University, 2023)
This research aims to explore the dynamics of group communication in the dissemination of development innovations within the Department of Communications and Informatics in North Sumatra Province. This study adopts a qualitative approach using the Case Study model. Data collection involves four techniques: (1) interviews, (2) participant observation, (3) documentation studies, and (4) reference searches. Informants were selected using the purposive sampling technique and snowball sampling. Data analysis follows the Miles, Huberman, and Spradley model, encompassing three steps: data reduction, data presentation, and drawing or verifying conclusions. The study's findings reveal that group communication within the Department revolves around the division and detailed allocation of tasks and responsibilities to individual employees. The dissemination of development innovations in North Sumatra utilises diverse communication techniques, encompassing brochures, posters, billboards, banners, television, RRI, websites, and email as the media for group communication programs.